PENGARUH HUMAN RESOURCES DAN KNOWLEDGE MANAGEMENT TERHADAP KINERJA KARYAWAN DI MEDIASI OLEH KUALITAS INFORMASI - Faiq Husni; Moch. Ali Shahab (Jurnal Riset Bisnis Indonesia, 2016)
The role of human resources became one of the key success factors, the BMT to face thecompetition. BMT rapid industrial growth brings the consequence of the great need for competenthuman resources in terms of quantity and quality. In addressing these conditions BMT has a strategyand putting human resource development as a key to success to win the competition. Issues to beanalyzed in this study are how the human resources of the quality of information, how the influenceof knowledge management on the quality of information, how to influence human resources toemployee performance, how the influence of knowledge management on employee performanceand how to influence the quality of information on employee performance. Samples taken in thisstudy were 80 respondents who become employees of BMT in Pekalongan. Analysis tools used arevalidity and reliability, the classic assumption and path analysis. The test results directly influencehuman resources and knowledge management on the quality of information obtained results thatsimultaneous human resources and knowledge management in a positive and significant effect onthe quality of information. While partially human resources and significant positive effect on thequality of information, knowledge management was no significant effect on the quality of information.Results of testing the effect of indirect human resources, knowledge management to employeeperformance through the quality of information obtained results that simultaneous human resources,knowledge management and information quality in a positive and significant influence on employeeperformance. Partial test results show that each variable research human resources, knowledgemanagement and information quality and significant positive effect on employee performance.Keywords: human resources, knowledge management, information quality and employeeperformance.